2011
DOI: 10.1111/j.1439-0531.2011.01843.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for the Establishment of Pregnancy in the Pig

Abstract: ContentsEstablishment of pregnancy in pigs requires continuous function of corpora lutea and endometrial preparation for embryo implantation. Progesterone regulates expression of many proteins necessary for endometrial remodelling and embryo-maternal communications. Attaining the uterine receptivity involves progesterone priming and loss of progesterone receptors in the uterine epithelium before days 10-12 after oestrus. Spermatozoa and oocytes in oviduct alter secretion of specific proteins that exert benefic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
77
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 113 publications
(267 reference statements)
0
77
0
Order By: Relevance
“…The early pregnancy in the pig is divided into three periods: post-conception (days 1-10 of pregnancy), the maternal recognition of pregnancy (days 11-13) and implantation (days 14-19) (Zięcik et al 2011). In our previous study we showed that the presence of embryos increased contractile activity in the porcine myometrium on days 12-14 of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…The early pregnancy in the pig is divided into three periods: post-conception (days 1-10 of pregnancy), the maternal recognition of pregnancy (days 11-13) and implantation (days 14-19) (Zięcik et al 2011). In our previous study we showed that the presence of embryos increased contractile activity in the porcine myometrium on days 12-14 of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, by inhibiting IL2 and expression of its receptor in human decidua, PGE2 was shown to block activation of maternal leukocytes with potential anti-trophoblast function, thereby revealing an immunosuppressive but embryo-protective effect (Parhar et al 1989 ). The embryo-and luteo-protective role of endometrial PGE2 has been discussed for pigs, in which additionally, speciesspecifi cally, estrogen also increases PGE2 secretion (see review Ziecik et al 2011 ). Similar effects could also apply to the canine species as suggested by the concomitantly and abundantly expressed PTGES levels in hatched compared to unhatched preimplantation embryos (Kautz et al 2014 ).…”
Section: Prostaglandinsmentioning
confidence: 92%
“…If not, PGF2α will be secreted by uterine capillaries, causing luteolysis (Senger, 1997). At the time of maternal recognition of pregnancy blastocytes will undergo a morphological transformation from a spherical to filamentous shape 10 mm in diameter around d 11.5 (Geisert et al, 1982;Ziecik, 2011). The elongation of filamentous forms will exceed 60 to 100 cm and complete this process by d 13 (Anderson, 2009).…”
Section: Swine Estrous Cyclementioning
confidence: 99%